2021
DOI: 10.1123/ijspp.2020-0706
|View full text |Cite
|
Sign up to set email alerts
|

A Sleep Analysis of Elite Female Soccer Players During a Competition Week

Abstract: Purpose: (1) To compare the sleep of female players from a professional soccer team to nonathlete controls across an in-season week and (2) to compare the sleep of core and fringe players from the same team on the night after a match to training nights. Methods: Using an observational design, 18 professional female soccer players and 18 female nonathlete controls were monitored for their sleep via wristwatch actigraphy across 1 week. Independent-sample t tests and Mann–Whitney U tests were performed to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Despite the controversial literature about sleep disturbances in females' athletes [11,12,13,17] our results support the presence of a higher percent of sleepiness in female soccer players compared to males. This result is consistent with another study in Spanish professional football players performed during a lockdown, who showed men having better sleep quality than women during the isolation period [9].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Despite the controversial literature about sleep disturbances in females' athletes [11,12,13,17] our results support the presence of a higher percent of sleepiness in female soccer players compared to males. This result is consistent with another study in Spanish professional football players performed during a lockdown, who showed men having better sleep quality than women during the isolation period [9].…”
Section: Discussionsupporting
confidence: 47%
“…There is some evidence among professional soccer players that males have a better sleep quality than women during the isolation period [9]. However, also in normal life conditions, sleep disturbances in females' soccer players has been only recently studied [5], showing a high incidence of sleep disturbance associated with the night pre-game [12] , post-game or post training [13] with a decrease in sleep time in those conditions . Female sleep has been shown also to be sensitive to menstrual cycle [14] which in turn affect arousal control, stress response, and memory consolidation [14].…”
Section: Ofmentioning
confidence: 99%
“…Across two seasons, basketball players experienced an 11% reduction in TST the night after doubleheaders compared to regular rounds of competition (p = 0.007) [ 48 ]. A recent study from Thomas et al [ 50 ] demonstrated that core (i.e. starting, n = 10) soccer players experienced later bedtimes on the night after a game (+ 37 min; p = 0.032) compared to training nights, alongside reduced sleep duration (−49 min; p = 0.010).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these findings, this study also compared the sleep of the soccer players (n = 18) to an age and sex matched non-athletic control group (n = 18) during a week encompassing the demands of training and competition. In this cohort, the soccer players had greater sleep duration than non-athletes (+38 min; p = 0.009), potentially due to their earlier bedtimes (−31 min; p = 0.047) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation